Laser-Assisted Facelift - Holcomb, J. David (Facial Plastic Surgery, 2014)
A variety of factors influence successful face and neck lift outcomes. Limited incision and/or dissection approaches as well as more traditional approaches impose certain limitations on surgeons' ability to effectively manage lower facial fullness and jowl ptosis. Laser-assisted facial contouring using a thermally confined 1,444 nm Nd:YAG micropulsed interstitial fiber laser enables precision volumetric reduction and shaping of lower facial fullness; the closed technique also predissects and facilitates greater vertical repositioning of an extended facelift flap. Use of the thermally confined 1,444 nm Nd:YAG micropulsed interstitial fiber laser in the neck (laser-assisted neck contouring) brings a similar benefit in predissecting, debulking, and shaping the neck and also significantly impacts surgical management of the platysma. This article focuses on methodology and benefits as well as limitations and complications of the laser-assisted facelift.
Keywords: facelift; neck lift; Nd:YAG fiber laser; facial contouring; platysmaplasty